Gerakan Masyarakat Cerdas Menggunakan Obat ( GEMA CERMAT ) Di Kampung Baru Kecamatan Galang - Delladari Mayefis; Reny Haryani; Shinta Sari Dewi; Sri Hainil; Andi Bunga Dahlia; Faziyana Faziyana; Merry Ardini; Selawati Selawati (Jurnal Pengabdian Ilmu Kesehatan, 2021)
There are still many problems with drug use among the public, including: Purchasing drugs not from licensed/official facilities, purchasing prescription drugs, purchasing antibiotics freely without a doctor's prescription, excessive use of over-the-counter drugs (over dosage), occurrence of side effects, drug interactions or misuse. Medicines often occur in society and can cause new health problems, there are still many people who do not understand how to store and dispose of medicines properly